ENHANCING COMMUNITY NUTRITIONAL SUFFICIENCY THROUGH HOME VEGETABLE GARDENING WITH PHYTOHORMONE-ENRICHED LIQUID ORGANIC FERTILIZER: A CASE STUDY OF CIBEBER II VILLAGE, BOGOR REGENCY, WEST JAVA PROVINCE - Munawir, Abdillah; Rusdiyanto, Edi; Naili Muna, Siti Umamah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The community service project is located in Cibeber II Village, Bogor Regency, with easy access to the sub-district capital of Leuwiliang. Cibeber II Village is predominantly characterized by extensive agricultural and plantation land; however, much of this land remains underutilized and lacks sustainable productivity. The community engagement method includes discussions and hands-on activities with local farmer groups, represented by housewives, focusing on the importance of organic vegetable cultivation techniques, the production of phytohormone-enriched liquid organic fertilizer, and simple methods for home vegetable gardening. The activities related to home vegetable gardening and the production of liquid organic fertilizer from household onion waste in Cibeber II Village received an overwhelmingly positive response from the community. This program not only enhances household food security and nutritional quality but also helps reduce household expenses.